PERLINDUNGAN KONSUMEN TERHADAP PENJUALAN ROKOK KEPADA ANAK DI BAWAH UMUR DI KOTA PEKANBARU - Rahmayeti '; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Consumers whose existence is unlimited, with very varied strata causes producers toengage in the marketing and distribution of products or services in ways that are as effective aspossible in order to reach a very diverse consumer. World health experts through manyresearch and research proved that cigarettes are very harmful to the health of the body.Regulation of the Government of the Republic of Indonesia Number 109 Year 2012 ConcerningSecurity of Materials Containing Addictive Substances in the form of Tobacco Products forHealth in Article 25 states Everyone is prohibited from selling tobacco products: (1) Using selfservicemachines; (2) To children under the age of 18 (eighteen) years and; (3) To pregnantwomen. The purpose of this research, namely; First, Knowing how the protection of children asconsumers of the sale of cigarettes to minors in the city pekanbaru. Second, Knowing whatcauses business actors to sell cigarettes to minors. Third, Knowing what efforts the governmentcan take in preventing children as consumers of cigarette sales to minors.The type of research used by the authors is sociological law research is a study thatexamines the legal aspects by looking at applicable legislation and compare with theimplementation in the field by way of survey. This study was conducted in Pekanbaru City,while the population and sample were the whole parties concerned with the research, the datasource used, the primary data, the secondary data and the tertiary data, the data collectiontechnique in this study by observation, interview, and library stusi .From the results of research problems there are three points that can be concluded.First, the legal protection of children as consumers of cigarette sales is still not workingproperly. De facto there are still many violations, so the child is still the target of cigarette salesbusiness. Secondly, businesses that sell cigarettes to children under the age of 18 (eighteen)years do not know that this is prohibited by legislation. Third, the government's efforts toregulate the age limit of cigarette consumers, however, the regulation does not run optimallywithout supervision. The author's suggestion, Firstly, It is expected that the consumer in thiscase the child under the age of 18 (eighteen) years get more supervision from parents, family,and teachers in his school. So with the supervision, the children will be educated and know whatthings are allowed and which they should not do. Secondly, it is expected that business actorsshould prioritize the rights of their consumers, providing clear information so that goods aretraded right on target. Make a more assertive warning in every cigarette sales business thatconsumers are entitled to buy cigarettes is the age above 18 (delpan) year. Third, Suggested tothe Government in this case Disperindag Pekanbaru degan cooperation with related agenciessuch as Health Office, Education Office, etc .. As supervisor, the mediator present to providesocialization to business actors and consumers in this case is a child under 18 (eighteen) yearsof existing laws and regulations.Keywords: Protection - Consumer - Child - Cigarette